Cross-hierarchical corticothalamic plasticity in the mouse visual system - Giasafaki, C (2019)
Almost all sensory information reached our brain via the thalamus. The thalamus is considered the relay center for sensory information to the cortex and has an essential role in the regulation of fundamental brain processes, including sleep, alertness, consciousness and cognition, via various distinct nuclei. Specifically in the visual system, inputs from the retina project to the “first-order” dorsal lateral geniculate nucleus (dLGN) of the thalamus, which projects to the primary visual cortex (V1). Layer V neurons selectively project to the “higher-order” lateral posterior nucleus (LP) and do not normally innervate dLGN. It has been recently proposed by Grant et al., (2016), that layer V projections rewire to innervate dLGN fter monocular enucleation (MoE); however, the cortical origin of these projections has not been determined. In my study, I examined neuronal rewiring of cortical layer V projections and their plasticity to structurally rearrange following neonatal MoE. After performing MoE in layer V-labelled transgenic mice (Rbp4-Cre::tdTomato) at birth, I studied the effects on the ingrowth of tdTomato-labelled corticofugal projections into visual thalamic nuclei, the dLGN and the LP. In order to investigate the corical origin of aberrant layer V projections in the sensory deprived dLGN, I performed AAV viral injections in the primary visual (V1) and somatosensory (S1) cortices of adult Rbp4-Cre::tdTomato mice (n=3 for V1, n=3 for S1) that had been monocularly enucleated at birth. My findings indicate innervation of layer V corticothalamic (GFP+) axons in the lower part of dLGN and LP only from V1 with formation of aberrant side branches and VGluT1+ boutons in the deprived dLGN. No alterations in the S1 projections to thalamus were observed following MoE with S1 axons completely bypassing dLGN. However, projections from A1 or other sources, such as secondary cortical areas, should also be further investigated. What is more, an increase in the bouton density was identified in the dLGN after input deprivation. Additionally, I examined the molecular changes induced by MoE in the thalamus at P8 by in situ hybridization and confirmed differential pattern of expression in control and deprived dLGN (n=3). Otx2 and Cbln2 showed increased expression in deprived dLGN accompanied by upregulation of gene expression in vLGN. Kcnk9 and Calb2 were downregulated in dLGN upon enucleation, also showing increased expression in vLGN. EphA5 was differentially expressed in dLGN and LP in control hemisphere with dLGN showing stronger labelling, whereas this difference was no longer evident after enucleation in dLGN of reduced volume. All the aforementioned results demonstrate the necessity of peripheral input for proper layer V axonal ingrowth, synaptic formation and transcriptional profile of the dlGN and might indicate its importance in the establishment of the specific characteristics of each order of thalamic nuclei.